Answer:
x^2+4x-4
Step-by-step explanation:
4x+1+x^2-5
x^2+4x-4
Step-by-step explanation:
m1.m2= -1
(4y = -2x -9)= (y = -1x/2 -9/4)
-1/2.m2= -1
m2 = 2
formula = y - y1 = m2 ( x - x1)
y - 10 = 2 ( x - (-7))
y - 10 = 2x + 14
y = 2x + 24
Answer:
cant not see the photo honey
Step-by-step explanation:
Answer:
3/10 and 4/10 4/12 and 9/12
Step-by-step explanation:
Checking the <span>discontinuity at point -4
from the left f(-4) = 4
from the right f(-4) = (-4+2)² = (-2)² = 4
∴ The function is continues at -4
</span>
<span>Checking the <span>discontinuity at point -2
from the left f(-2) = </span></span><span><span>(-2+2)² = 0
</span>from the right f(-2) = -(1/2)*(-2)+1 = 2
∴ The function is jump discontinues at -2
</span>
<span>Checking the <span>discontinuity at point 4
from the left f(4) = </span></span><span><span>-(1/2)*4+1 = -1
</span>from the right f(4) = -1
but there no equality in the equation so,
</span><span>∴ The function is discontinues at 4
The correct choice is the second
point </span>discontinuity at x = 4 and jump <span>discontinuity at x = -2</span>